Analysis of Dynamic Archives Management - Ahmad Rifa'i; Feri Fadli Rizki; Lina Hadriyanti (ijd-demos, 2024)
Abstract This study aims to examine: 1) the management of active records, 2) obstacles in the implementation of active records management, and 3) efforts to overcome obstacles in active records management at the Rancaseneng Village Office, Cikeusik District, Pandeglang Regency. This is a descriptive study employing a qualitative approach. The study involved five informants: the Village Head, the Village Secretary, and three section/division heads at the Rancaseneng Village Office. Data collection techniques included observation, interviews, and documentation analysis. Data analysis involved data collection, data reduction, data presentation, and conclusion drawing. Data validity was verified through source and method triangulation. The results indicate that, in general, active records management at the Rancaseneng Village Office encompasses: 1) Active record creation, covering the generation of incoming and outgoing correspondence. 2) Record usage, involving the borrowing of records (using loan slips) and record retrieval (using control cards and search lists). 3) Record maintenance, performed by cleaning dust from records using a feather duster. 4) Record disposition (weeding/reduction), conducted annually. 5) Factors influencing records management include: a) the use of a control card system, a classification code filing system, and a combined centralization-decentralization approach; b) inadequate facilities due to insufficient budget allocation; c) a shortage of records staff and a lack of specialized educational backgrounds in records management among existing staff; and d) adequate room lighting, though the temperature remains suboptimal. Obstacles encountered include: hampered management due to inadequate facilities; a shortage of staff and a lack of necessary skills and knowledge among records personnel; and suboptimal record maintenance. Efforts to overcome obstacles include: submitting a proposal for additional funding to procure archiving facilities; maximizing the use of existing infrastructure and equipment; optimizing the assignment of qualified personnel to archiving roles; and regularly cleaning archives to prevent damage. Keywords: active records management, Pandeglang, archives